Measuring students’ statistical reasoning abilities using flipped classroom model with SPSS and STATCAL - Ramadhani, Rahmi; Evans, Brian (Universitas Papua, 2022)
The development of Technology, Information and Communication (ICT) in education has been growing considerably. Use of technologies contribute to supporting student learning and play a vital role in the learning process. The Covid-19 pandemic, since early 2020, has impacted the implementation of the learning process, especially in higher education. The learning instruction has shifted from face-to-face to online learning (e-learning). It is undeniable that the learning process experiences disruptions, resulting in significant changes in the learning environment. Thus, the flipped classroom model is likely to be on model for educators in higher education. This study aims to investigate an increase in the statistical reasoning abilities of engineering students taught using the flipped classroom model assisted by SPSS and STATCAL applications analyzed based on gender. Participants involved 55 first-year informatics engineering students. Data were collected using a test in the form of essay questions and then analyzed using the stacking method of the Rasch measurement model. The results showed that the statistical reasoning abilities of students improved after being taught using the flipped classroom model with the SPSS and STATCAL applications. This finding implies that the flipped classroom model assisted by SPSS and STATCAL applications is effectively implemented in technology-integrated statistics learning.